Role of progesterone supplementation in estrus induction in Murrah buffaloes under field conditions in non-breeding season - Sharma, Karan; Phogat, Jagat Bir; Pandey, Anand Kumar; Dhaka, Aman Parkash; Singh, Shobna; Ghadwal, Sonu (Buffalo Bulletin, 2021)
The objective of present study was to assess the effect of Modified Co-synch protocol with or without progesterone device on estrus induction and conception rate in Murrah buffaloes under field conditions during summer season. The study was conducted on 30 postpartum anestrous Murrah buffaloes, divided into two groups containing 15 animals in each group. All animals were of parity between 2nd to 5th and body condition score of more than 3. Group 1 animals were treated with Modified Co-synch protocol. In Group 2 animals, in addition to Modified Co-synch protocol progesterone device was supplemented exogenously and kept in situ for 7 days. Another objective of study was to estimate plasma progesterone concentration on different days of protocols in both the groups. In Group 1, out of 15 animals that received Modified Co-synch protocol treatment, 12 (80%) animal responded and exhibited signs of heat after the prostaglandin administration and out of which four animal (33.33%) exhibited excellent symptoms, five animals (41.7%) showed medium category estrus and only three animal (25%) responded with poor estrus symptoms. Similarly in Group 2, all 15 animals that received Modified Co-synch protocol along with progesterone device for 7 days responded to treatment and expressed sign of heat and out of which seven buffaloes (46.7%) responded with excellent symptoms, five animals (33.3 %) showed medium estrus symptoms and only three animals (20%) expressed poor estrus signs. In Group 1, out of 12 animals which were inseminated, five animals (33.3%) were found to be pregnant after FTAI at induced estrus and three animals (30%) got pregnant following AI during second estrus. Thus, an overall conception rate (53.53%) with pregnancy of eight buffaloes following induced and subsequent estrous was achieved in this Group. Similarly in Group 2, out of 15 animals, seven buffaloes (46.6%) were found to be pregnant following induced estrous and three animals (37.5%) got pregnant following AI at subsequent estrous. Thus, an overall conception rate (66.67%) with pregnancy of ten buffaloes following induced and subsequent estrous was recorded in this group. Concentration of progesterone in Group 1 was 0.24±0.04, 1.38±0.11, 0.31±0.05, 0.25±0.04 ng/ml (on Day 0, 7, 9, 10) and in Group 2 was 0.26±0.04, 3.75±0.40, 0.24±0.05, 0.25±0.05 ng/ml (on Day 0, 7, 9, 10). Therefore, it was concluded that progesterone supplementation in Modified Co-synch protocol treatment during non-breeding season results in very good induction and acceptable conception rate in anestrous buffaloes under field conditions.